2015
DOI: 10.1097/mpg.0000000000000565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Colon Transection on Spontaneous and Meal‐Induced High‐Amplitude–Propagating Contractions in Children

Abstract: Background After Hirschsprung’s disease (HD) surgery, many children suffer fecal incontinence caused by increased number of high amplitude propagating contractions (HAPCs) propagating through the neorectum to the anal verge. The aim of this study was to determine whether children with HD have more HAPCs than children with colon transections for reasons other than HD. Methods We reviewed 500 colon manometries. Children (7.6±5.1 yrs; 275 male) with functional constipation (n=237; 7.4±5.0yrs; 126 male) and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…For instance, the maximum dose ranges between 5 and 10 mg and only a single intraluminal stimulation is usually suggested with only few studies reporting the use of either two doses or a single higher dose. 7,9,[15][16][17][18][19][20][21] In the present study, the additional higher dose of bisacodyl (0.4 mg/kg up to a maximum of 20 mg) significantly increased the number of HAPCs throughout the entire colon, improved the propagation of HAPCs toward the distal colon, and sharpened the morphology of pressure waves within HAPCs. This suggests that this higher dose may be more effective compared with lower doses in assessing the residual function of colonic motor activity and in discriminating between those patients with normal colonic motor activity from those with localized segmental abnormalities.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…For instance, the maximum dose ranges between 5 and 10 mg and only a single intraluminal stimulation is usually suggested with only few studies reporting the use of either two doses or a single higher dose. 7,9,[15][16][17][18][19][20][21] In the present study, the additional higher dose of bisacodyl (0.4 mg/kg up to a maximum of 20 mg) significantly increased the number of HAPCs throughout the entire colon, improved the propagation of HAPCs toward the distal colon, and sharpened the morphology of pressure waves within HAPCs. This suggests that this higher dose may be more effective compared with lower doses in assessing the residual function of colonic motor activity and in discriminating between those patients with normal colonic motor activity from those with localized segmental abnormalities.…”
Section: Discussionsupporting
confidence: 53%
“…To date, there is a still considerable inconsistency regarding the dose of bisacodyl that should infused intraluminally during manometric recording. For instance, the maximum dose ranges between 5 and 10 mg and only a single intraluminal stimulation is usually suggested with only few studies reporting the use of either two doses or a single higher dose . In the present study, the additional higher dose of bisacodyl (0.4 mg/kg up to a maximum of 20 mg) significantly increased the number of HAPCs throughout the entire colon, improved the propagation of HAPCs toward the distal colon, and sharpened the morphology of pressure waves within HAPCs.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…A recent report highlighted the association between bisacodyl‐induced HAPC and anal canal relaxation (a “colo‐anal reflex”), with most contractions resulting in anal canal relaxation as HAPC reach the splenic flexure . After any type of colonic transection, CM has demonstrated that there is an increase in the number of HAPCs, probably due to the loss of a negative recto‐colonic feedback, with a higher frequency of propagated contractions occurring in those patients operated for Hirschsprung's disease compared to those undergoing surgery for other indications …”
Section: Discussionmentioning
confidence: 99%
“…35 After any type of colonic transection, CM has demonstrated that there is an increase in the number of HAPCs, probably due to the loss of a negative recto-colonic feedback, with a higher frequency of propagated contractions occurring in those patients operated for Hirschsprung's disease compared to those undergoing surgery for other indications. 36 It is obvious that interpretation of colon manometry studies requires experience and sub-specialty training. In the Guidelines for Training in Pediatric Gastroenterology by NASPGHAN published in 2013 it is stated that pediatric GI fellows should be exposed to this procedure but the numbers of studies required for the training were not specified.…”
Section: Discussionmentioning
confidence: 99%